PEMANFAATAN MEDIA PEMBELAJARAN SENI RUPA DI SMP N 34 PADANG - Ikhsan Maulana, Dra. Zubaidah, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2018)
The purpose of this study was to find out how the use of fine arts learning media in SMP N 34 Padang. This type of research is qualitative using descriptive methods. Data collection procedure is by observation to collect data, interviewing to get information about the types of learning media, the use of learning media, and documentation. The informants consisted of cultural arts teachers, curriculum vice principal and students at SMP N 34 Padang. The result of the research is learning media has not been applied in all art learning materials, only at practice materials.Keywords: media, learning,fine art, used